PERMUKIMAN RAWA DI KALIMANTAN SELATAN - , Andy Safariansyah ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Swamp settlements at Sungai Buluh village, Rantau Bujur and Mantaas had unique features. The uniqueness is not only in settlement patterns but also in the form of socio cultural behaviour of the people. The socio cultural behavior of people in swamp settlement then became local wisdom that reflected in spatial and environmental management in that area. This research used inductive qualitative method by using phenomenological approach. All the data and information obtained by observations and interviews, then analyzed resulting in keywords that became themes concept found from this research. The research indicated that there was a local wisdom in spatial pattern both at macro and micro scale. It could be seen in the form of dividing of residency and business area, system of land ownership, residency adaptation, pattern and orientation of settlement and integration of social space. Such, local wisdom in is also seen in environmental management in the forms of local knowledge of climates and season estimations, knowledge of fishing techniques, farming, lowland swamp farming system, management of water system and system of keeping farm animals especially herding swamp buffalo. Besides, the research also indicated how strong the people's socio cultural life which describe that they are the hardworkers, creative, humble and helping each other that formed by historical experiences and environment.